In vitro Evaluation of Shear Bond Strength of Orthodontic Brackets Bonded with Different Adhesives - Shaik, Junaid Ahmed (Contemp Clin Dent, 2018)
BACKGROUND: There is necessary of dry operating field for bonding of orthodontic brackets. The presence of moisture can alter the bond strength. Hence, the aim of the present study was to evaluate the shear bond strength of orthodontic brackets with different adhesives. MATERIALS AND METHODS: In this in vitro study, a total of 100 orthodontically extracted premolars with sound crown structure were divided into 4 equal groups of different primers. Bonding on the buccal surface of all teeth was done after acid etching with upper premolar brackets using different primers followed by light curing. Shear bond strength was evaluated with or without salivary contamination with both adhesives. A shear force for deboning the bracket was done with universal testing machine. The debonded specimens were examined at ×10 magnification to check site of bond failure and remaining adhesive on tooth using adhesive remnant index (ARI). The obtained data were statistically evaluated using SPSS 20 for Windows (SPSS Inc., Chicago, IL, USA) using ANOVA, Kolmogorov–Smirnov, and Levene's test at the statistical significance of P < 0.05. RESULTS: Transbond Plus showed higher shear bond strength of 8.92 MPa under dry and 5.65 MPa with saliva contamination over Transbond XT of 7.24 MPa under dry and 2.43 MPa with saliva contamination, respectively. Higher ARI score was found without contamination in both adhesives. CONCLUSION: Transbond Plus hydrophilic resin had good shear bond strength under both dry and contamination condition compared to hydrophobic Transbond XT resin material.